Impact of sample history and solvent effects on pathway control in the supramolecular polymerisation of Au(i)-metallopeptide amphiphiles. Issue 16 (6th April 2023) - Thomas, Marius; Lewe, Vanessa; Kölsch, Jonas; Urschbach, Moritz; Erlenbusch, Jessica; Stach, Oliver Sven; Besenius, Pol
Abstract : We investigate the kinetics of the supramolecular polymerisation of an Au(i )-metallopeptide amphiphile that assembles into exceptionally long and rigid nanofibers. Abstract : We investigate the kinetics of the supramolecular polymerisation of an Au(i )-metallopeptide amphiphile that assembles into exceptionally long and rigid nanofibers. We developed a precise preparation protocol to measure the concentration dependent assembly kinetics which elucidated a nucleation–elongation dominated supramolecular polymerisation process. We show striking differences in the assembly behavior and morphology in aqueous media, even at organic solvent contents as low as 1 vol%, compared to pure buffer.